Correction: Tracer kinetic modeling of a 14 kDa anti-CD8 PET tracer (2C8v144) for in vivo estimation of CD8 expression in tissue and blood, binding affinity, and total body receptor occupancy - Ruediger E. Port; C. Andrew Boswell; Annie Ogasawara; Herman Gill; Jan Marik; Alice F. Tarantal; Eric Berg; Simon P. Williams; Gregory Z. Ferl (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Urban climate evaluation in the upcoming generation of CMIP6-Driven EURO-CORDEX regional climate simulations - Javier Diez-Sierra; Natalia Zazulie; Gaby S. Langendijk; Yaiza Quintana; Marianna Adinolfi; May Bohmann; Lars Buntemeyer; Erasmo Buonomo; Steven Caluwaerts; Angelo Campanale; Rita M. Cardoso; David Carvalho; et al. (Urban Climate, 2026)

Glacio-eustasy during the early Bajocian peak cooling events (Middle Jurassic) - Stéphane Bodin; Julien Talon; Jesper Allan Frederiksen; Clemens Ullmann; Simon Andrieu; François-Nicolas Krencker; Alicia Fantasia; Jan Danisch; Lahcen Kabiri (Global and Planetary Change, 2026)

Tracer kinetic modeling of a 14 kDa anti-CD8 PET tracer (2C8v144) for in vivo estimation of CD8 expression in tissue and blood, binding affinity, and total body receptor occupancy - Ruediger E. Port; C. Andrew Boswell; Annie Ogasawara; Herman Gill; Jan Marik; Alice F. Tarantal; Eric Berg; Simon P. Williams; Gregory Z. Ferl (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Repairing of in-mold electronics and life cycle assessment - Stephan Harkema; Diana E. Godoi Bizarro; Maarten H. Bakker; Jan P.H. van Delft; Pim R. Ostendorf; Peter A. Rensing; Lia de Simon; A. van Schaik (Resources, Conservation and Recycling, 2026)

FarmLCA: A novel approach to assess agroecological innovations in Life Cycle Assessment - Simon Moakes; Philipp Oggiano; Jan Landert; Catherine Pfeifer; Laura de Baan (Agricultural Systems, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

Circular food systems in Kenya: Exploring the role of livestock - Dagmar J.M. Braamhaar; Benjamin van Selm; Jan van der Lee; Simon J. Oosting (Agricultural Systems, 2026)

Spaceborne estimates of canopy temperature and soil moisture predict daily and annual subalpine tree growth - Eli W. Estey; Jan U.H. Eitel; Lee A. Vierling; Grace L. Peven; Kerry A. Cawse-Nicholson; Simon J. Hook; Kevin L. Griffin (Agricultural and Forest Meteorology, 2026)

A dynamic model for Waddington’s landscape accounting for cell-to-cell communication - Simon Merkt; Lara Fuhrmann; Erika Dudkin; Andreas Schlitzer; Barbara Niethammer; Jan Hasenauer (Mathematical Biosciences, 2025)

Hybrid plant-dairy cheese: Effects of lactic acid bacteria and plant proteins on composition, proteolysis, and flavor profile - Huabin Luo; Simen Akkermans; Wim Engels; Simon Jacobs; Herwig Bachmann; Jan F.M. Van Impe; Marjon H.J. Wells-Bennik (Food Chemistry, 2025)

New chlorophylls designed by theoretical spectroscopy and machine learning - Fabian Weber; Simon Petry; Dennis J. Nürnberg; Jan P. Götze (Photosynthesis Research, 2025)
The main pigment for oxygenic photosynthesis, chlorophyll (Chl) a , is structurally related to several other Chl variants, naturally occurring mostly with mono-oxidized substitutions. These include Chl b , Chl d and Chl f and divinyl chlorophylls (DVChls) a and b . In this contribution, we computationally explore an expanded set of over 250,000 Chl variants, looking for potentially interesting targets for synthetic biology. We focus on optical properties, employing a machine learning (ML) approach and subsequently verifying the corresponding predictions using time-dependent density functional theory (TD-DFT) and multireference DFT (DFT/MRCI). We find that (i) Chl f is the best monosubstituted red-shifted Chl, as no other Chl in our set exceeds Chl f in terms of both red shift and absorption intensity, (ii) Chl b is not the best Chl to harvest photons from the green region of the optical spectrum, as several other Chls with the same or better green absorbance were identified (most notably DVChl b ) and (iii) the T 1 energy of Chls can be slightly adapted. The latter would enable experiments to determine whether it is beneficial having the T 1 transition energy located between the two lowest O 2 singlet state transitions, as it is found for Chl a . This might be a prerequisite for stable, efficient oxygen generation. Our ML approach thus provides a comprehensive overview on an extensive subset of potential Chl modifications that could be used for tuning oxygenic photosynthesis, if suitable synthesis pathways can be found.

Plankton communities today and tomorrow—potential impacts of multiple global change drivers and marine heatwaves - Cédric L. Meunier; Josefin Schmidt; Antonia Ahme; Areti Balkoni; Katharina Berg; Lea Blum; Maarten Boersma; Jan D. Brüwer; Bernhard M. Fuchs; Luis Gimenez; Maïté Guignard; Ruben Schulte‐Hillen; et al. (Limnology and Oceanography, 2025)
In the context of global change, marine organisms are subjected not only to gradual changes in abiotic parameters, but also to an increasing number of extreme events, such as heatwaves. However, we still know little about the influence of heatwaves on the structure of marine communities, and experimental studies are needed to test the impact of heatwaves alone and in combination with other environmental drivers. Here, we conducted a mesocosm experiment to assess the potential impact of heatwaves on plankton communities, which we did under ambient and future environmental conditions. To simulate future environmental conditions, we simultaneously manipulated temperature and pH based on IPCC predictions for 2100, and dissolved N : P ratios based on the conditions expected in European coastal zones. While we did not observe any effects of simulated heatwaves on phytoplankton abundances, we identified that future environmental conditions may favor smaller phytoplankton species and that additional heatwaves may especially favor small phytoflagellates and coccolithophores. We also observed that future environmental conditions may reduce the abundances and modify the species composition of bacterioplankton, microzooplankton, and mesozooplankton, and that heatwaves may exacerbate these effects. Using a unique approach to examine the potential impacts of heatwaves under current and future environmental conditions on a natural multi‐trophic marine plankton community, we show that the combination of multiple global change drivers has the potential to perturb the entire basis of marine food webs.

Discovery of a mud‐covering cephalopod evidences the complex life habits in the abyss - Alejandra Mejía‐Saenz; Bethany F. M. Fleming; Daniel O. B. Jones; Loïc Van Audenhaege; Henk‐Jan Hoving; Erik Simon‐Lledó (Ecology, 2025)

Performance of Atlantic salmon reared under three different regimes of continuous aerobic exercise during the freshwater phase - Ana S. Gomes; Pablo Balseiro; Mari D. Iversen; Fabian Zimmermann; Munetaka Shimizu; Ayaka Izutsu; Amaya Albalat; Cindy Pedrosa; Richard Broughton; Sara Calabrese; Marnix Gorissen; Jan Zethof; et al. (Aquaculture, 2025)

Towards better tailored new entrant support in European agriculture: Analysing the differences between family successors and newcomers - Simon Stork; Wolf Lorleberg; Bernd Pölling; Xiaohua Yu; Jan-Henning Feil (Journal of Rural Studies, 2025)

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Physiological responses of Arctic and Baltic Sea populations of toxigenic Alexandrium ostenfeldii (Dinophyceae) to different climate change stressors - Simon Tulatz; Urban Tillmann; Bernd Krock; Jan Tebben; Cédric Leo Meunier (Harmful Algae, 2025)

Assessing the chemical burden of the North-East Atlantic ecosystem through targeted and untargeted HRMS-based approaches - Georgios Gkotsis; Maria-Christina Nika; Nikiforos Alygizakis; Konstantinos Vasilatos; Antonia Athanasopoulou; Jonathan L. Barber; Rob Berbee; Thierry Burgeot; Susana Galante Oliveira; Johan Gustafsson; Alejandro Iglesias Campos; Ulrike Kammann; et al. (Journal of Hazardous Materials, 2025)

Elemental and isotopic signatures of Asteroid Ryugu support three early Solar System reservoirs - Quinn R. Shollenberger; Jan Render; Josh Wimpenny; Rosalind M.G. Armytage; Nipun Gunawardena; John M. Rolison; Justin I. Simon; Gregory A. Brennecka (Earth and Planetary Science Letters, 2025)

Pollen presentation mitigates competition for pollinators due to diurnal stratification of pollen transfer - Jakub Štenc; Lukáš Janošík; Martin Freudenfeld; Eva Matoušková; Jiří Hadrava; Michael Mikát; Klára Daňková; Tereza Hadravová; Tadeáš Ryšan; Jasna Simonová; Klára Koupilová; Alice Haveldová; et al. (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Unveiling genetic diversity in jute mallow (Corchorus spp.): morphological clustering reveals distinctive traits among accessions from Africa and Asia - Pamela M.K. Afokpe; Serge Ologou; Sehou Romaric Kouiho; Simon Jan de Hoop; Sognigbé N’Danikou; Enoch G. Achigan-Dako; M. Eric Schranz (Genetic Resources and Crop Evolution, 2025)

Improving effective antimicrobial resistance (AMR) prevention in ambulatory care: lessons from secondary appraisal of Belgian anti-infectious treatment care guidelines - Johan Van Laethem; Simon Planken; Pieter-Jan Cortoos; Marie-Angélique De Scheerder; Maja Kiselinova; Anne Tilmanne; Erlangga Yusuf; Johan Vansintejan; Nicolas Dauby (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Cauliflower centre detection and 3-dimensional tracking for robotic intrarow weeding - Axel Willekens; Bert Callens; Francis Wyffels; Jan G. Pieters; Simon R. Cool (Precision Agriculture, 2025)

From rural to urban: Exploring livestock farming practices in urbanizing landscapes - Dagmar J.M. Braamhaar; Jan van der Lee; Bockline O. Bebe; Simon J. Oosting (Agricultural Systems, 2025)

Metacommunity Theory and Metabarcoding Reveal the Environmental, Spatial and Biotic Drivers of Meiofaunal Communities in Sandy Beaches - Maximilian Pichler; Simon Creer; Alejandro Martínez; Diego Fontaneto; Willem Renema; Jan‐Niklas Macher (Molecular Ecology, 2025)
Understanding the processes that shape community assembly is a critical focus of ecology. Marine benthic meiofauna, microscopic invertebrates inhabiting sediment environments, play important roles in ecosystem functioning but have been largely overlooked in metacommunity studies due to the lack of community data. In this study, we quantify the relative contributions of environmental filtering, spatial processes, and biotic associations in structuring meiofaunal communities. We applied Generalised Dissimilarity Modelling (GDM) and Joint Species Distribution Modelling (JSDM) to an extensive metabarcoding dataset comprising 550 samples collected from sandy beaches along over 650 km of the Dutch and German North Sea coast. Our findings reveal that biotic associations, followed by environmental factors, particularly the distance from the low tide line and sediment grain size, are primary drivers of meiofauna community turnover, highlighting the influence of sharp environmental gradients. Spatial factors indicating dispersal limitations have no major impact on community composition, supporting the assumption that microscopic organisms have strong dispersal capabilities. JSDM results demonstrate that while species sorting is a key driver of community assembly, environmental factors are most important in environmentally distinct (‘extreme’) sites, whereas biotic associations significantly shape community assembly in both environmentally similar and dissimilar habitats, emphasising the need to incorporate species interactions into models of community assembly. By providing insights into the drivers of meiofaunal community structure, our study highlights the importance of environmental gradients and biotic associations in shaping biodiversity patterns and underscores the potential for similar approaches to enhance understanding of other ecosystems with small, highly diverse, but understudied taxa.

Associations between metabolomic scores and clinical outcomes in hospitalized COVID-19 patients - Jens A. Venema; Anna Kuranova; Daniele Bizzarri; Simon P. Mooijaart; Angele P. M. Kerckhoffs; Kitty Slieker; Evertine J. Abbink; Harmke A. Polinder-Bos; Eline Slagboom; Geeske Peeters; Jacobijn Gussekloo; Karel G. M. Moons; et al. (GeroScience, 2025)
The disease course and outcome of COVID-19 greatly varies between individuals. To explore which biological systems may contribute to this variation, we examined how individual metabolites and three metabolic scores relate to COVID-19 outcomes in hospitalized COVID-19 patients. The metabolome of 346 patients was measured using the 1H-NMR Nightingale platform. The association of individual metabolomic features and multi-biomarker scores, i.e. MetaboHealth, MetaboAge, and Infectious Disease Score (IDS) (higher scores reflect poorer health), with in-hospital disease course, long-term recovery, and overall survival were analyzed. Higher values for the metabolites phenylalanine (HR = 1.33, CI = 1.14–1.56), glucose (HR = 1.37, CI = 1.16–1.62) and lactate (HR = 1.38, CI = 1.16–1.63) were associated with mortality. For all three metabolic scores, higher scores were significantly associated with higher odds of a poorer in-hospital disease course (MetaboHealth: OR = 1.61, CI = 1.29–2.02; ΔMetaboAge: OR = 1.42, CI = 1.16–1.74; IDS: OR = 1.55, 1.25–1.93) and with overall survival (MetaboHealth: HR = 1.57, CI = 1.28–1.92; ΔMetaboAge: HR = 1.34, CI = 1.15–1.57; IDS: HR = 1.56, CI = 1.27–1.93). MetaboHealth and ΔMetaboAge showed a stronger association in younger patients (< 70 yrs.) than older patients. No clear patterns were found in associations between the three scores and measures of long-term recovery. In conclusion, the heterogeneity in disease course after SARS-COV2 infection may be explained either by generic biological frailty reflected by the three metabolomics scores or by glycemic control (glucose, lactate) and respiratory distress (phenylalanine).

DEEM — Differential Evolution with Elitism and Multi-populations - Jan Machaček; Simon Siegel; Hauke Zachert (Swarm and Evolutionary Computation, 2025)

Evaluation of ecosystem functions across three ecosystem types in afromontane forest in Kenya - Felistas Mbinya Mwania; Simon Mwangi Muriu; Virginia Gathoni Gichuru; Mike Teucher; Jan Christian Habel (International Journal of Tropical Insect Science, 2025)

Isotopic labeling of nanoparticles for the evaluation of their environmental fate in mesocosm experiments - George Metreveli; Sandra Kurtz; Simon Lüderwald; Mirco Bundschuh; Jan David; Allan Philippe; Reinhard Schneider; Natalia P. Ivleva; Anna Baskal; Laura Degenkolb; Ralf Schulz; Gabriele E. Schaumann (Science of The Total Environment, 2024)

Tiny but mighty mayfly - probing Prosopistoma pennigerum (Müller 1785) as the Flagship species for the Vjosa Wild River National Park - Thea Schwingshackl; Jan Martini; Mourine Yegon; Gabriel Singer; Simon Vitecek (Journal of Insect Conservation, 2024)
The recently created Vjosa Wild River National Park sets precedence at the European scale to protect a rare river ecosystem and, at the same time, the last refuge of the almost extinct mayfly Prosopistoma pennigerum (Müller 1785, Fig. 1). We extensively searched for the species in the Vjosa and five abiotically similar but fragmented surrounding rivers. To characterize the genetic diversity of the Vjosa population and assess its potential as a source population, we analysed partial mtCOI data. Besides high abundances in the Vjosa River, we observed only a few specimens in the free-flowing section of the Osumi River, but in no other investigated river although suitable habitat appears to be widely available at site-scale. Molecular analysis of 174 specimens revealed largely homogeneous sequences across all sampling sites and an almost 100% infection rate with Wolbachia sp. that suggests parthenogenetic reproduction, possibly as a strategy to increase resilience to high natural disturbance dynamics. We argue that P . pennigerum should serve as a flagship species for the Vjosa Wild River National Park. The species is exceptionally aesthetic, and its most viable, but apparently parthenogenetic populations are restricted to the Vjosa River where the species is widespread. The restricted regional distribution indicates only weak (or no) potential to recolonize and/or re-establish in other rivers, and the absence from fragmented rivers suggests dependence on high ecological integrity. Implications for conservation: Our findings thus sanction our nomination of P . pennigerum as the flagship species for the Vjosa Wild River National Park.

Network analysis to reveal the most commonly detected compounds in predator-prey pairs in freshwater and marine mammals and fish in Europe - Nikiforos Alygizakis; Niki Kostopoulou; Georgios Gkotsis; Maria-Christina Nika; Anastasia Orfanioti; Kelsey Ng; Erasmia Bizani; Varvara Nikolopoulou; Alexander Badry; Andrew Brownlow; Cinzia Centelleghe; Elizabeth A. Chadwick; et al. (Science of The Total Environment, 2024)

Monitoring and perception of allergenic pollen in urban park environments - Nadja Kabisch; Thomas Hornick; Jan Bumberger; Roland Krämer; Rupert Legg; Oskar Masztalerz; Maximilian Bastl; Jan.C. Simon; Regina Treudler; Susanne Dunker (Landscape and Urban Planning, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Late Quaternary hydroclimate variability in Madagascar and its connection to atmospheric circulation patterns - Christos Katrantsiotis; Simon Haberle; Anneli Ekblom; Rienk H. Smittenberg; Jan Risberg; Susan Rule; Geoff Clark; Atholl Anderson; Amy Prendergast; Aaron Carmens; Chantal Radimilahy; Lucien Rakotozafy; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mutant PTPMT1 disrupts cardiolipin metabolism and mitochondrial bioenergetics leading to a neurodevelopmental syndrome - Micol Falabella; Chiara Pizzamiglio; Luis Carlos Tabara; Benjamin Munro; Mohamed S. Abdel-Hamid; Ece Sonmezler; William L. Macken; Shanti Lu; Lisa Tilokani; Padraig J. Flannery; Simon A.S. Pope; Simon J.R. Heales; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

How inquilinism shaped breeding systems in a termite host‐inquiline relationship - Johanne Timmermans; Simon Hellemans; Jan Křivánek; Esra Kaymak; Nicolas Fontaine; Thomas Bourguignon; Robert Hanus; Yves Roisin (Molecular Ecology, 2024)
Social insects have developed a broad diversity of nesting and foraging strategies. One of these, inquilinism, occurs when one species (the inquiline) inhabits the nest built and occupied by another species (the host). Obligatory inquilines must overcome strong constraints upon colony foundation and development, due to limited availability of host colonies. To reveal how inquilinism shapes reproductive strategies in a termite host‐inquiline dyad, we carried out a microsatellite marker study on Inquilinitermes inquilinus and its host Constrictotermes cavifrons . The proportion of simple, extended and mixed families was recorded in both species, as well as the presence of neotenics, parthenogenesis and multiple foundations. Most host colonies (95%) were simple families and all were monodomous. By contrast, the inquiline showed a higher proportion of extended (30%) and mixed (5%) families, and frequent neotenics (in 25% of the nests). This results from the simultaneous foundation in host nests of numerous incipient colonies, which, as they grow, may compete, fight, or merge. We also documented the use of parthenogenesis by female–female pairs. In conclusion, the classical monogamous colony pattern of the host species suggests uneventful development of simple foundations dispersed in the environment, in accordance with the wide distribution of their resources. By contrast, the multiple reproductive patterns displayed by the inquiline species reveal strong constraints on foundation sites: founders first concentrate into host nests, then must attempt to outcompete or absorb the neighbouring foundations to gain full control of the resources provided by the host nest.

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Correction: Effects of individual traits vs. trait syndromes on assemblages of various herbivore guilds associated with central European Salix - Jing V. Leong; Priscila Mezzomo; Petr Kozel; Tereza Volfová; Paola de Lima Ferreira; Carlo L. Seifert; Phillip T. Butterill; Inga Freiberga; Jan Michálek; Pável Matos-Maraví; Alexander Weinhold; Marica T. Engström; et al. (Oecologia, 2024)

Effects of individual traits vs. trait syndromes on assemblages of various herbivore guilds associated with central European Salix - Jing V. Leong; Priscila Mezzomo; Petr Kozel; Tereza Volfová; Paola de Lima Ferreira; Carlo L. Seifert; Phillip T. Butterill; Inga Freiberga; Jan Michálek; Pável Matos-Maraví; Alexander Weinhold; Marica T. Engström; et al. (Oecologia, 2024)

Special issue opening editorial: Designing, assessing and scaling approaches for integrated seed sector development - Walter Simon de Boef; Berber Kramer; Deborah Nabuuma; Chris O. Ojiewo; David J. Spielman; Tjeerd-Jan Stomph (Agricultural Systems, 2024)

Unraveling the complexity: A taxonomy for characterizing and structuring smart energy services in the building sector - Lukas Fabri; Jan Weissflog; Simon Wenninger (Journal of Cleaner Production, 2024)

Towards operational UAV-based forest health monitoring: Species identification and crown condition assessment by means of deep learning - Simon Ecke; Florian Stehr; Julian Frey; Dirk Tiede; Jan Dempewolf; Hans-Joachim Klemmt; Ewald Endres; Thomas Seifert (Computers and Electronics in Agriculture, 2024)

The Cologne ECMM Excellence Center: A Two-Year Analysis of External Consultation Service for Invasive Fungal Infections - Jon Salmanton-García; Philipp Koehler; Jan-Hendrik Grothe; Sibylle C. Mellinghoff; Ertan Sal; Michaela Simon; Jannik Stemler; Oliver A. Cornely; Rosanne Sprute (Mycopathologia, 2024)
The European Confederation of Medical Mycology (ECMM), formed due to the surge in invasive fungal infections (IFI), initiated the Excellence Centers program in 2016 to guide stakeholders to leading medical mycology sites. This report focuses on the Cologne ECMM Excellence Center, recognized with Diamond status for active global involvement in 2017. The center offers free consultation via email and phone, responding within 24 h for life-threatening IFI, collecting data on origin, pathogens, infection details, and more. Over two years, 189 requests were received globally, predominantly from Germany (85%), mainly involving Aspergillus spp., Mucorales, and Candida spp. Fungal mixed infections occurred in 4% of cases. The center's service effectively addresses IFI challenges, advocating for a comprehensive study encompassing all ECMM Excellence Centers to enhance global mycological care. Proactive expansion of consultancy platforms is crucial, with future analyses needed to assess expert advice's impact on patient outcomes.

The present and future contribution of ships to the underwater soundscape - Luca Possenti; Lennart de Nooijer; Christ de Jong; Frans-Peter Lam; Simon Beelen; Johan Bosschers; Tom van Terwisga; Rens Stigter; Gert-Jan Reichart (Frontiers in Marine Science, 2024)
Since the industrial revolution the ocean has become noisier. The global increase in shipping is one of the main contributors to this. In some regions, shipping contributed to an increase in ambient noise of several decibels, especially at low frequencies (10 to 100 Hz). Such an increase can have a substantial negative impact on fish, invertebrates, marine mammals and birds interfering with key life functions (e.g. foraging, mating, resting, etc.). Consequently, engineers are investigating ways to reduce the noise emitted by vessels when designing new ships. At the same time, since the industrial revolution (starting around 1760) greenhouse gas emissions have increased the atmospheric carbon dioxide fraction x (CO 2 ) by more than 100 μmol mol -1 . The ocean uptake of approximately one third of the emitted CO 2 decreased the average global surface ocean pH from 8.21 to 8.10. This decrease is modifying sound propagation, especially sound absorption at the frequencies affected by shipping noise lower than 10 kHz, making the future ocean potentially noisier. There are also other climate change effects that may influence sound propagation. Sea surface warming might alter the depth of the deep sound speed channel, ice melting could locally decrease salinity and more frequent storms and higher wind speed alter the depth of the thermocline. In particular, modification of the sound speed profile can lead to the appearance of new ducts making specific depths noisier. In addition, ice melting and the increase in seawater temperature will open new shipping routes at the poles increasing anthropogenic noise in these regions. This review aims to discuss parameters that might change in the coming decades, focusing on the contribution of shipping, climate change and economic and technical developments to the future underwater soundscape in the ocean. Examples are given, contrasting the open ocean and the shallow seas. Apart from the changes in sound propagation, this review will also discuss the effects of water quality on ship-radiated noise with a focus on propeller cavitation noise.

Late Pleistocene to modern precipitation changes at the Paranal clay pan, central Atacama Desert - Volker Wennrich; Christoph Böhm; Dominik Brill; Rafael Carballeira; Dirk Hoffmeister; Andrea Jaeschke; Florian Kerber; Antonio Maldonado; Simon Matthias May; Lester Olivares; Stephan Opitz; Janet Rethemeyer; et al. (Global and Planetary Change, 2024)

Meta-review on Perforation Model of Subarachnoid Hemorrhage in Mice: Filament Material as a Possible Moderator of Mortality - Serdar Alpdogan; Timo Sander; Rui Zhang; Dilaware Khan; Xuanchen Li; Huakang Zhou; Ke Li; Ann-Christin Nickel; Baolong Zheng; Anastasiya Skryabin; Simon Schieferdecker; Björn B. Hofmann; et al. (Translational Stroke Research, 2024)
Robust preclinical models are inevitable for researchers to unravel pathomechanisms of subarachnoidal hemorrhage (SAH). For the mouse perforation model of SAH, the goal of this meta-review was the determination of variances in mortality, SAH severity grade, and vasospasm, and their experimental moderators, as many researchers are facing with incomparable results. We searched on the databases PubMed , Embase , and Web of Science for articles describing in vivo experiments using the SAH perforation mouse model and measuring mortality, SAH grade, and/or vasospasm. After screening, 42 articles (total of 1964 mice) were included into systematic review and meta-analysis. Certain model characteristics were insufficiently reported, e.g., perforation location (not reported in six articles), filament (material ( n = 15) and tip texture ( n = 25)), mouse age ( n = 14), and weight ( n = 10). Used injective anesthetics and location of perforation showed large variation. In a random-effects meta-analysis, the overall animal mortality following SAH was 21.3% [95% CI: 17.5%, 25.7%] and increased with longer observational periods. Filament material significantly correlated with animal mortality ( p = 0.024) after exclusion of hyperacute studies (time after SAH induction < 24 h). Reported mean SAH grade was 10.7 [9.6, 11.7] on the scale of Sugawara (J Neurosci Methods 167:327–34, 2008). Furthermore, mean diameter of large cerebral arteries after SAH was reduced by 27.6% compared to sham-operated non-SAH mice. Uniforming standards of experimental procedures and their reporting are indispensable to increase overall comparability.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Reevaluation and novel insights into amino sugar and neutral sugar necromass biomarkers in archaea, bacteria, fungi, and plants - Erika Salas; Markus Gorfer; Dragana Bandian; Stephanie A. Eichorst; Hannes Schmidt; Julia Horak; Simon K.-M. R. Rittmann; Christa Schleper; Barbara Reischl; Thomas Pribasnig; Jan Jansa; Christina Kaiser; et al. (Science of The Total Environment, 2024)

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Mobile measurements for distribution and attribution of particulate matter in urban environments - Lorenz Harr; Tim Sinsel; Helge Simon; Max Carl Arne Torbenson; Esper Jan (Atmospheric Environment, 2023)

Bioactivity-guided isolation of toosendanin and salanninolide from Melia volkensii and their antifeedant activity against economically important insect pests - Victor Jaoko; Clauvis Nji Tizi Taning; Simon Backx; Pierfrancesco Motti; Jackson Mulatya; Jan Vandenabeele; Titus Magomere; Florence Olubayo; Guy Smagghe; Stefaan P.O. Werbrouck; Sven Mangelinckx (Crop Protection, 2023)

Evolutionary diversity of proton and water channels on the oxidizing side of photosystem II and their relevance to function - Rana Hussein; Mohamed Ibrahim; Asmit Bhowmick; Philipp S. Simon; Isabel Bogacz; Margaret D. Doyle; Holger Dobbek; Athina Zouni; Johannes Messinger; Vittal K. Yachandra; Jan F. Kern; Junko Yano (Photosynthesis Research, 2023)
One of the reasons for the high efficiency and selectivity of biological catalysts arise from their ability to control the pathways of substrates and products using protein channels, and by modulating the transport in the channels using the interaction with the protein residues and the water/hydrogen-bonding network. This process is clearly demonstrated in Photosystem II (PS II), where its light-driven water oxidation reaction catalyzed by the Mn 4 CaO 5 cluster occurs deep inside the protein complex and thus requires the transport of two water molecules to and four protons from the metal center to the bulk water. Based on the recent advances in structural studies of PS II from X-ray crystallography and cryo-electron microscopy, in this review we compare the channels that have been proposed to facilitate this mass transport in cyanobacteria, red and green algae, diatoms, and higher plants. The three major channels (O1, O4, and Cl1 channels) are present in all species investigated; however, some differences exist in the reported structures that arise from the different composition and arrangement of membrane extrinsic subunits between the species. Among the three channels, the Cl1 channel, including the proton gate, is the most conserved among all photosynthetic species. We also found at least one branch for the O1 channel in all organisms, extending all the way from Ca/O1 via the ‘water wheel’ to the lumen. However, the extending path after the water wheel varies between most species. The O4 channel is, like the Cl1 channel, highly conserved among all species while having different orientations at the end of the path near the bulk. The comparison suggests that the previously proposed functionality of the channels in T. vestitus (Ibrahim et al., Proc Natl Acad Sci USA 117:12624–12635, 2020; Hussein et al., Nat Commun 12:6531, 2021) is conserved through the species, i.e. the O1-like channel is used for substrate water intake, and the tighter Cl1 and O4 channels for proton release. The comparison does not eliminate the potential role of O4 channel as a water intake channel. However, the highly ordered hydrogen-bonded water wire connected to the Mn 4 CaO 5 cluster via the O4 may strongly suggest that it functions in proton release, especially during the S 0 → S 1 transition (Saito et al., Nat Commun 6:8488, 2015; Kern et al., Nature 563:421–425, 2018; Ibrahim et al., Proc Natl Acad Sci USA 117:12624–12635, 2020; Sakashita et al., Phys Chem Chem Phys 22:15831–15841, 2020; Hussein et al., Nat Commun 12:6531, 2021).

Assessing labelled carbon assimilation from poly butylene adipate-co-terephthalate (PBAT) monomers during thermophilic anaerobic digestion - Jan Struckmann Poulsen; Alba Trueba-Santiso; Juan M. Lema; Simon Gregersen Echers; Reinhard Wimmer; Jeppe Lund Nielsen (Bioresource Technology, 2023)

The cumulative impacts of droughts and N deposition on Norway spruce (Picea abies) in Switzerland based on 37 years of forest monitoring - Simon Tresch; Tobias Roth; Christian Schindler; Sven-Eric Hopf; Jan Remund; Sabine Braun (Science of The Total Environment, 2023)

Polyhydroxyalkanoates (PHAs) synthesis and degradation by microbes and applications towards a circular economy - Wen Zhou; Simon Bergsma; Dana Irene Colpa; Gert-Jan Willem Euverink; Janneke Krooneman (Journal of Environmental Management, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Assessment of fertilization strategies and policy measures for vegetables by simulation of a long-term cauliflower leek rotation - Jérémie Haumont; Jan Diels; Eddie Schrevens; Simon Cool; Peter Lootens; Wouter Saeys (European Journal of Agronomy, 2023)

Social harvest control rules for sustainable fisheries - Kate M. Barclay; Simon R. Bush; Jan Jaap Poos; Andries Richter; Paul A. M. van Zwieten; Katell G. Hamon; Eira Carballo‐Cárdenas; Annet P. Pauwelussen; Rolf A. Groeneveld; Hilde M. Toonen; Amanda Schadeberg; Marloes Kraan; et al. (Fish and Fisheries, 2023)
Fisheries are supposed to be for the benefit of society, producing food, providing livelihoods and enabling cultural continuity. Biological productivity goals for fish stocks operationalised through Harvest Control Rules (HCRs) are central to contemporary fisheries management. While fisheries policies often state socio‐economic objectives, such as enhancing the livelihoods of coastal communities, those are rarely, if ever, incorporated into operationalised management procedures. The lack of articulation of social objectives and lack of monitoring of social outcomes around HCRs amounts to poor public policy. In this article, we explore the potential for social HCRs (sHCRs) with reference points and agreed predefined actions to make the social dimensions of fisheries explicit. sHCRs cannot cover all social dimensions, so should be considered as one tool within a broader framework of fisheries governance. Moreover, successful sHCRs would require sound deliberative and participatory processes to generate legitimate social objectives, and monitoring and evaluation of fisheries management performance against those objectives. We introduce two potential types of sHCRs, one based on allocation of catch within biological limit reference points, and one for when fishing exceeds biological limit reference points. The application of sHCRs, we argue, can foster accountability and help avoid non‐transparent negotiations on size and distribution of the catch. Our proposal is a call to action for policy makers and fisheries managers to properly integrate social criteria into fisheries governance, and for both biophysical fisheries scientists and social scientists to do better in practical collaboration for methods and knowledge development to support this integration.

Quantification and characterization of PFASs in suspended particulate matter (SPM) of German rivers using EOF, dTOPA, (non-)target HRMS - Fabian Simon; Lennart Gehrenkemper; Susanne Becher; Georg Dierkes; Nicole Langhammer; Antje Cossmer; Marcus von der Au; Bernd Göckener; Annette Fliedner; Heinz Rüdel; Jan Koschorreck; Björn Meermann (Science of The Total Environment, 2023)

Major fine-scale spatial heterogeneity in accumulation of gelatinous carbon fluxes on the deep seabed - Henk-Jan Hoving; Antje Boetius; Katherine Dunlop; Jens Greinert; Matthias Haeckel; Daniel O. B. Jones; Erik Simon-Lledó; Yann Marcon; Tanja Stratmann; Inken Suck; Andrew K. Sweetman; Autun Purser (Frontiers in Marine Science, 2023)
Abyssal plain communities rely on the overlying water column for a settling flux of organic matter. The origin and rate of this flux as well as the controls on its fine-scale spatial distribution following seafloor settlement are largely unquantified. This is particularly true across regions where anthropogenically-induced seafloor disturbance has occurred. Here, we observed, quantified and mapped a mass deposition event of gelatinous zooplankton carcasses (pyrosomes) in July-September 2015 across one such physically disturbed region in the Peru Basin polymetallic nodule province (4150 m). Seafloor in this area was disturbed with a plough harrow in 1989 (as part of the DISCOL experiment) causing troughs in the sediment. Other parts were disturbed with an epibenthic sled (EBS) during a cruise in 2015 resulting in steep-walled, U-shaped troughs. We investigated two hypotheses: a) gelatinous food falls contribute significantly to the abyssal plain carbon pump and b) physical seafloor disturbance influences abyssal distribution of organic matter. We combined optical and bathymetric seafloor observations, to analyze pyrosome distribution on seabeds with different levels of disturbance. 2954 pyrosome colonies and associated taxa were detected in > 14,000 seafloor images. The mean regional carbon (C) deposition associated with pyrosome carcasses was significant compared to the flux of particulate organic C (182 to 1543%), and the total respired benthic C flux in the DISCOL Experimental Area (39 to 184%). EBS-disturbed seafloor tracks contained 72 times more pyrosome-associated C than an undisturbed reference site, and up to 4 times more than an area disturbed in 1989. Deposited pyrosomes collected had a higher proportion of labile fatty acids compared to the sediment. We document the temporal and spatial extent of an abyssal food fall event with unprecedented detail and show that physical seafloor disturbance results in the accumulation of detrital material. Such accumulation may reduce oxygen availability and alter benthic community structure. Understanding both the relevance of large food falls and the fine scale topography of the seafloor, is necessary for impact assessment of technologies altering seafloor integrity (e.g. as a result of bottom-trawling or deep seabed mining) and may improve their management on a global scale.

A synthesis of a coastal northern pike (Esox lucius) fishery and its social-ecological environment in the southern Baltic Sea: Implications for the management of mixed commercial-recreational fisheries - Robert Arlinghaus; Timo Rittweg; Félicie Dhellemmes; Dieter Koemle; Rob van Gemert; Hendrik Schubert; Dominique Niessner; Sören Möller; Jan Droll; René Friedland; Wolf-Christian Lewin; Malte Dorow; et al. (Fisheries Research, 2023)

pyerrors: A python framework for error analysis of Monte Carlo data - Fabian Joswig; Simon Kuberski; Justus T. Kuhlmann; Jan Neuendorf (Computer Physics Communications, 2023)

Current Potential for Clinical Optimization of Social Cognition Assessment for Frontotemporal Dementia and Primary Psychiatric Disorders - Jan Van den Stock; Maxime Bertoux; Janine Diehl-Schmid; Olivier Piguet; Katherine P. Rankin; Florence Pasquier; Simon Ducharme; Yolande Pijnenburg; Fiona Kumfor (Neuropsychology Review, 2023)

Immune cell targeted fumaric esters support a role of GPR109A as a primary target of monomethyl fumarate in vivo - Simon Straß; Johanna Geiger; Natascha Cloos; Nadja Späth; Sophia Geiger; Anna Schwamborn; Luciano De Oliveira da Cunha; Mariella Martorelli; Jan-Hinrich Guse; Thaisa Lucas Sandri; Michael Burnet; Stefan Laufer (Inflammopharmacology, 2023)

Endangered spined loach Cobitis species in Southwest Germany: A complex network of native, hybrid and newly emerged populations - Samuel Roch; Patrick Bartolin; Pascal Vonlanthen; Jan Baer; Simon Grundmüller; Laura S. Epp; Alexander Brinker (Fisheries Management and Ecology, 2023)
Successful conservation of cryptic species such as representatives of the genus Cobitis presents a challenge for fishery managers. Only Cobitis taenia L. is currently assumed to occur in southwest Germany, where it is classified as critically endangered. Established genetic markers and eDNA analysis identified three Cobitis species in the study area. Cobitis taenia and Cobitis elongatoides were widely distributed in the Rhine River system, primarily forming hybrid species complexes in which polyploid individuals dominate but coexist with diploid parent species. A third non‐native species, Cobitis bilineata , has recently become established in the southern part of the Rhine to which it probably migrated naturally via the connected Aare River system. In the Danube River catchment, two populations, including one previously thought to be extinct, comprise both diploid and polyploid representatives of C. elongatoides . Our results provide an important basis for more targeted conservation strategies for Cobitis species currently found in the region.

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Biochar impacts on runoff and soil erosion by water: A systematic global scale meta-analysis - Behrouz Gholamahmadi; Simon Jeffery; Oscar Gonzalez-Pelayo; Sergio Alegre Prats; Ana Catarina Bastos; Jan Jacob Keizer; Frank G.A. Verheijen (Science of The Total Environment, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Isostearic acid is an active component of imiquimod formulations used to induce psoriaform disease models - Simon Straß; Johanna Geiger; Mariella Martorelli; Sophia Geiger; Natascha Cloos; Manuel Keppler; Tina Fischer; Laura Riexinger; Anna Schwamborn; Jamil Guezguez; Nadja Späth; Santiago Cruces; et al. (Inflammopharmacology, 2023)

Primary cordierite with > 2.5 wt% CO2 from the UHT Bakhuis Granulite Belt, Surinam: CO2 fluid phase saturation during ultrahigh-temperature metamorphism - Emond W. F. de Roever; Simon L. Harley; Jan M. Huizenga (Contributions to Mineralogy and Petrology, 2023)
The Paleoproterozoic Bakhuis Granulite Belt (BGB) in Surinam, South America, shows ultrahigh-temperature metamorphism (UHTM) at temperatures of around 1000 °C which, unusually, produced peak-to-near-peak cordierite with sillimanite and, in some cases, Al-rich orthopyroxene on a regional scale. Mg-rich cordierite (Mg/(Mg + Fe) = 0.88) in a sillimanite-bearing metapelitic granulite has a maximum birefringence of second-order blue (ca. 0.020) indicative of a considerable amount of CO 2 (> 2 wt%) within its structural channels. SIMS microanalysis confirms the presence of 2.57 ± 0.19 wt% CO 2 , the highest CO 2 concentration found in natural cordierite. This high CO 2 content has enabled the stability of cordierite to extend into UHT conditions at high pressures and very low to negligible H 2 O activity. Based on a modified calibration of the H 2 O–CO 2 incorporation model of Harley et al. (J Metamorph Geol 20:71–86, 2002), this cordierite occupies a stability field that extends from 8.8 ± 0.6 kbar at 750 °C to 11.3 ± 0.65 kbar at 1050 °C. Volatile-saturated cordierite with 2.57 wt% CO 2 and negligible H 2 O (0.04 wt%) indicates fluid-present carbonic conditions with a CO 2 activity near 1.0 at peak or near-peak pressures of 10.5–11.3 kbar under UHT temperatures of 950–1050 °C. The measured H 2 O content of the cordierite in the metapelite is far too low to be consistent with partial melting at 1000–1050 °C, implying either that nearly all of any H 2 O originally in this cordierite under UHT conditions was lost during post-peak cooling or that the cordierite was formed after migmatization. The high level of CO 2 required to ensure fluid saturation of the c. 11 kbar UHT cordierite is proposed to have been derived from an external, possibly mantle, source.

Exploring macroinvertebrate biodiversity in the dynamic southern Balkan stream network of the Vjosa using preservative-based DNA metabarcoding - Marie V. Brasseur; Jan Martini; Olivia Wilfling; Remo Wüthrich; Emil Birnstiel; Rebecca Oester; Vera M. A. Zizka; Gabriel Singer; Florian Leese; Simon Vitecek (Aquatic Sciences, 2023)
Reliable biodiversity data are crucial for environmental research and management. Unfortunately, data paucity prevails for many regions and organismal groups such as aquatic invertebrates. High-throughput DNA-based identification, in particular DNA metabarcoding, has accelerated biodiversity data generation. However, in the process of metabarcoding, specimens are usually destroyed, precluding later specimen-based analyses. Metabarcoding of DNA released into the preservative ethanol has been proposed as a non-destructive alternative, but proof-of-principle studies have yielded ambiguous results, reporting variance in detection probability for various taxa and methodological biases. In this study, we tested the performance of preservative-based metabarcoding of aquatic invertebrates in comparison to a standard morpho-taxonomic assessment based on samples from one of Europe’s last free-flowing rivers, the Vjosa. Multi-habitat samples were collected at 43 sites in two seasons and stored in ethanol, after fixation in formaldehyde for morpho-taxonomic analyses. Preservative-based DNA metabarcoding detected three times more taxa but failed to detect other taxa found using the standard method. In addition to incomplete reference data and primer bias that likely precluded the detection of specific taxa, preservative-based DNA metabarcoding cannot provide accurate abundance estimates. However, the metabarcoding data revealed distinct small-scale and large-scale community patterns in the Vjosa river network, which were also recovered by quantitative data of the standard approach. Overall, our results indicate that preservative-based metabarcoding provides important biodiversity data, which could be further improved by quantitative validation. The method is robust and reliable, even though samples were taken under harsh field-conditions and stored without cooling. Further, our results emphasise the need for reliable DNA barcoding reference libraries. Building those may be supported by preservative-based metabarcoding that maintains intact vouchers for subsequent specimen-based analyses.

Reducing anthelmintic inputs in organic farming: Are small ruminant farmers integrating alternative strategies to control gastrointestinal nematodes? - Caroline Chylinski; Spiridoula Athanasiadou; Susann Thüer; Christian Grovermann; Simon Moakes; Hervé Hoste; Saulius Petkevicius; Cynthia Verwer; Jan Verkaik; Steffen Werne (Veterinary Parasitology, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Spatial clusters of Varroa destructor control strategies in Europe - Robert Brodschneider; Johannes Schlagbauer; Iliyana Arakelyan; Alexis Ballis; Jan Brus; Valters Brusbardis; Luis Cadahía; Jean-Daniel Charrière; Robert Chlebo; Mary F. Coffey; Bram Cornelissen; Cristina Amaro da Costa; et al. (Journal of Pest Science, 2023)
Beekeepers have various options to control the parasitic mite Varroa destructor in honey bee colonies, but no empirical data are available on the methods they apply in practice. We surveyed 28,409 beekeepers maintaining 507,641 colonies in 30 European countries concerning Varroa control methods. The set of 19 different Varroa diagnosis and control measures was taken from the annual COLOSS questionnaire on honey bee colony losses. The most frequent activities were monitoring of Varroa infestations, drone brood removal, various oxalic acid applications and formic acid applications. Correspondence analysis and hierarchical clustering on principal components showed that six Varroa control options (not necessarily the most used ones) significantly contribute to defining three distinctive clusters of countries in terms of Varroa control in Europe. Cluster I (eight Western European countries) is characterized by use of amitraz strips. Cluster II comprises 15 countries from Scandinavia, the Baltics, and Central-Southern Europe. This cluster is characterized by long-term formic acid treatments. Cluster III is characterized by dominant usage of amitraz fumigation and formed by seven Eastern European countries. The median number of different treatments applied per beekeeper was lowest in cluster III. Based on estimation of colony numbers in included countries, we extrapolated the proportions of colonies treated with different methods in Europe. This suggests that circa 62% of colonies in Europe are treated with amitraz, followed by oxalic acid for the next largest percentage of colonies. We discuss possible factors determining the choice of Varroa control measures in the different clusters.

Mass falls of crustacean carcasses link surface waters and the deep seafloor - Erik Simon‐Lledó; Brian J. Bett; Noëlie M. A. Benoist; Henk‐Jan Hoving; Dmitry Aleynik; Tammy Horton; Daniel O. B. Jones (Ecology, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Concentrations of pesticide residues in fish tissue are below detectability in the Menoua River (West Cameroon) - Jose Innoncent Tamdjo Tache; Patricia Bi Asanga Fai; Simon Awafor Tamungang; Algrient Towa Nana; Jan Riegert (Environmental Monitoring and Assessment, 2023)

Coronary Artery Disease Detected by Low Frequency Heart Sounds - Samuel Emil Schmidt; Lene Helleskov Madsen; John Hansen; Henrik Zimmermann; Henning Kelbæk; Simon Winter; Dorte Hammershøi; Egon Toft; Johannes Jan Struijk; Peter Clemmensen (Cardiovascular Engineering and Technology, 2022)

Case design and flow resistance in high-alpine caddisfly larvae (Insecta, Trichoptera) - Johann Waringer; Simon Vitecek; Jan Martini; Carina Zittra; Ariane Vieira; Hendrik C. Kuhlmann (Hydrobiologia, 2022)
For evaluating hydraulic stress reduction strategies of caddisfly larvae, our study has three goals. First, creating a database on Reynolds numbers ( Re ) and drag coefficients valid for Limnephilidae larvae with cylindrical mineral cases. Second, evaluating the effects of submerged weight and biometry in cases with comparable length/width ratios. And third, collecting field data in an alpine environment for gaining insights into the hydraulic niches occupied by thirteen Drusinae species. Biometric data were subsequently combined with published Reynolds numbers and mean flow velocity data measured immediately upstream of Limnephilidae larvae at the moment of dislodgement. This provides drag coefficients for the range of Reynolds numbers obtained in the field. Data reveal that heavy cases strongly benefit from compensating drag by submerged weight, thereby enabling species to utilize high velocity spots, an important benefit for filtering species.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Mesenchymal Stem Cells From Mouse Hair Follicles Reduce Hypertrophic Scarring in a Murine Wound Healing Model - Hanluo Li; Mirjana Ziemer; Ivana Stojanovic; Tamara Saksida; Danijela Maksimovic-Ivanic; Sanja Mijatovic; Goran Djmura; Dragica Gajic; Ivan Koprivica; Tamara Krajnovic; Dijana Draca; Jan-Christoph Simon; et al. (Stem Cell Reviews and Reports, 2022)
Wound healing of acute full-thickness injuries and chronic non-healing ulcers leads to delayed wound closure, prolonged recovery period and hypertrophic scarring, generating a demand for an autologous cell therapy and a relevant pre-clinical research models for wound healing. In this study, an immunocompetent model for wound healing was employed using a syngeneic murine cell line of mesenchymal stem cells cultured from the mouse whisker hair follicle outer root sheath (named moMSCORS). moMSCORS were isolated using an air-liquid interface method, expanded in vitro and characterized according to the MSC definition criteria - cell viability, in vitro proliferation, MSC phenotype and multi-lineage differentiations. Moreover, upon applying moMSCORS in an in vivo full-thickness wound model in the syngeneic C57BL/6 mice, the treated wounds displayed different morphology to that of the untreated wound beds. Quantitative evaluation of angiogenesis, granulation and wound closure involving clinical scoring and software-based quantification indicated a lower degree of inflammation in the treated wounds. Histological staining of treated wounds by the means of H&E, Alcian Blue, PicroSirius Red and αSMA immune labelling showed lower cellularity, less collagen filaments as well as thinner dermal and epidermal layers compared with the untreated wounds, indicating a general reduction of hypertrophic scars. The decreased inflammation, accelerated wound closure and non-hypertrophic scarring, which were facilitated by moMSCORS, hereby address a common problem of hypertrophic scars and non-physiological tissue properties upon wound closure, and additionally offer an in vivo model for the autologous cell-based wound healing. Graphic Abstract

Genetic analysis of hog deer (Axis porcinus) in Victoria, Australia, and its applications to invasive species and game management - Erin Hill; Nicholas Murphy; Simon Toop; Adrian Linacre; Jan M. Strugnell (European Journal of Wildlife Research, 2022)
Hog deer were introduced to Australia in the 1860s, where they have spread across the Gippsland region of Victoria. Due to its status as an introduced species and an important game animal within Victoria, management of the species is complex. Given this complexity, genetic studies can provide important information regarding population structure and diversity which can assist in controlling problematic populations of hog deer, while also ensuring viable game stock in sites managed as game reserves. The aim of this study was to investigate the population genetic structure and diversity of the Victorian hog deer 150 years after introduction using short tandem repeats (STRs). Hog deer samples were collected across 15 sites of differing management regimes in the Gippsland region of Victoria and genotyped for 13 polymorphic STR loci. Up to four distinct genetic clusters were identified across the sites sampled, suggesting that despite low observed genetic diversity, population structure is present across their range. It was also possible to detect evidence of recent translocations among populations. This study suggests that the presence of distinct genetic clusters may enable management of separate genetic units, considering invasive species and game management objectives.

Changes in β‐diversity of saproxylic beetles along environmental gradients in temperate forests depend on species relative abundances - Pavel Sebek; Lukas Cizek; David Hauck; Jan Miklin; Ondrej Konvicka; Stepan Vodka; Simon Thorn (Journal of Biogeography, 2022)
Aim Understanding the processes that structure biological communities along environmental gradients remains one of the main aims of ecological research. A leading question is how differences in species composition between sites, that is, β‐diversity, change in habitats ordered along environmental gradients and how such changes vary with species relative abundances. The existing literature remains descriptive, mostly comparing communities from different parts of a gradient, but not tracking sequential changes of β‐diversity along the entire gradient. Location Temperate deciduous forests in Central Europe. Taxa Saproxylic beetles. Methods We applied a generalized concept of Hill numbers to data on the distribution of saproxylic beetles to test (i) whether community dissimilarities correlate with dissimilarities in major environmental variables (canopy openness, tree diameter and tree genus) and (ii) which mechanisms explain sequential changes of β‐diversity along these environmental gradients. Furthermore, we illustrate changes in the mean (α‐diversity) and total (γ‐diversity) number of species along the gradients. Results Dissimilarities in saproxylic beetle communities were positively correlated with dissimilarities in all studied environmental variables. Changes in β‐diversity along the gradients differed for different weighting of rare, common and dominant species, with rare and dominant species always showing opposite trends. β‐diversity increased simultaneously with increasing γ‐diversity when weight was given to dominant species. On the other hand, β‐diversity decreased when weight was given to rare species. Main conclusions The different response of rare and dominant species indicates a similar importance of stochastic and deterministic processes in determining β‐diversity. Although the changes in β‐diversity detected along the environmental gradients were relatively slight, major community dissimilarities were found when comparing communities in different locations of the environmental gradients.

Farmed animal production in tropical circular food systems - Simon Oosting; Jan van der Lee; Marc Verdegem; Marion de Vries; Adriaan Vernooij; Camila Bonilla-Cedrez; Kazi Kabir (Food Security, 2022)
In the discourse about the development of farmed animal production (terrestrial livestock production and aquaculture) in the tropics, two important food system outcomes emerge: (1) to supply animal-sourced food (ASF) at a level that suffices healthy future diets, including for poor people, and (2) to contribute to climate change mitigation and minimize pollution with nitrogen and phosphorus. Livestock production and aquaculture contribute to food security directly by increasing producers’ food diversity and availability, but also that of urban consumers, and indirectly through income generation and increased farm resilience. Recently, circularity has come to the fore as an integrated approach to food system development. Circularity has four cornerstones: (1) food crops have highest priority (which implies no food-feed competition), (2) avoid losses, (3) recycle waste and (4) use animals to unlock biomass that humans cannot eat. In this review, the role of farmed animals in circular food systems in the tropics is presented in four case studies and the impacts of circularity on food security and environmental impact mitigation are discussed. The cases are ruminants in grazing systems in West Africa and in Colombia, fish in pond aquaculture in general, and land-limited dairy production in Indonesia. Additionally, options for novel protein sources for use in livestock and fish feeding are presented. It is concluded that farmed animals are important in circular food systems because of their use of land unsuited for crop production, their upgrading of crop residues, and their supply of manure to crop production. Nevertheless, the increasing demand for ASF puts pressure on important characteristics of circularity, such as minimizing food-feed competition, maximization of use of waste streams in feed, and the value of manure for fertilization. Hence, in line with conclusions for Western countries, maximum circularity and sustainability of food systems can only be achieved by optimizing the population size of animals. Thus, a sustainable contribution of ASF production to global food security is complex and in not only a technical matter or outcome of an economic process balancing supply and demand. It requires governance for which public, private, and social actors need to partner.

Development of an STR panel for a non-native population of an endangered species - Erin Hill; Adrian Linacre; Simon Toop; Nicholas Murphy; Jan M. Strugnell (Molecular Biology Reports, 2022)

Demonstration of large area forest volume and primary production estimation approach based on Sentinel-2 imagery and process based ecosystem modelling - Jukka Miettinen; Simon Carlier; Lauri Häme; Annikki Mäkelä; Francesco Minunno; Juho Penttilä; Jan Pisl; Jussi Rasinmäki; Yrjö Rauste; Lauri Seitsonen; Xianglin Tian; Tuomas Häme (International Journal of Remote Sensing, 2021)

Contralateral strength training attenuates muscle performance loss following anterior cruciate ligament (ACL) reconstruction: a randomised-controlled trial - Claire Minshull; Peter Gallacher; Simon Roberts; Andrew Barnett; Jan Herman Kuiper; Andrea Bailey (European Journal of Applied Physiology, 2021)

DNA Metabarcoding Methods for the Study of Marine Benthic Meiofauna: A Review - Romy Gielings; Maria Fais; Diego Fontaneto; Simon Creer; Filipe Oliveira Costa; Willem Renema; Jan-Niklas Macher (Frontiers in Marine Science, 2021)
Meiofaunal animals, roughly between 0.045 and 1 mm in size, are ubiquitous and ecologically important inhabitants of benthic marine ecosystems. Their high species richness and rapid response to environmental change make them promising targets for ecological and biomonitoring studies. However, diversity patterns of benthic marine meiofauna remain poorly known due to challenges in species identification using classical morphological methods. DNA metabarcoding is a powerful tool to overcome this limitation. Here, we review DNA metabarcoding approaches used in studies on marine meiobenthos with the aim of facilitating researchers to make informed decisions for the implementation of DNA metabarcoding in meiofaunal biodiversity monitoring. We found that the applied methods vary greatly between researchers and studies, and concluded that further explicit comparisons of protocols are needed to apply DNA metabarcoding as a standard tool for assessing benthic meiofaunal community composition. Key aspects that require additional consideration include: (1) comparability of sample pre-treatment methods; (2) integration of different primers and molecular markers for both the mitochondrial cytochrome c oxidase subunit I (COI) and the nuclear 18S rRNA genes to maximize taxon recovery; (3) precise and standardized description of sampling methods to allow for comparison and replication; and (4) evaluation and testing of bioinformatic pipelines to enhance comparability between studies. By enhancing comparability between the various approaches currently used for the different aspects of the analyses, DNA metabarcoding will improve the long-term integrative potential for surveying and biomonitoring marine benthic meiofauna.

The Global Water Cycle Budget: A Chronological Review - Mijael Rodrigo Vargas Godoy; Yannis Markonis; Martin Hanel; Jan Kyselý; Simon Michael Papalexiou (Surveys in Geophysics, 2021)

Assessing the Impact of the Assimilation of SWOT Observations in a Global High-Resolution Analysis and Forecasting System – Part 2: Results - Babette C. Tchonang; Mounir Benkiran; Pierre-Yves Le Traon; Simon Jan van Gennip; Jean Michel Lellouche; Giovanni Ruggiero (Frontiers in Marine Science, 2021)
A first attempt was made to quantify the impact of the assimilation of Surface Water Ocean Topography (SWOT) swath altimeter data in a global 1/12° high resolution analysis and forecasting system through a series of Observing System Simulation Experiments (OSSEs). The OSSE framework (Nature Run and Free Run) and data assimilation scheme have been described in detail in a companion article ( Benkiran et al., 2021 ). The impact of assimilating data from SWOT and three nadir altimeters was quantified by estimating analysis and forecast error variances for sea surface height (SSH), temperature, salinity, zonal, and meridional velocities. Wave-number spectra and coherence analyses of SSH errors were also computed. SWOT data will significantly improve the quality of ocean analyses and forecasts. Adding SWOT observations to those of three nadir altimeters globally reduces the variance of SSH and surface velocities in analyses and forecasts by about 30 and 20%, respectively. Improvements are greater in high-latitude regions where space/time coverage of SWOT is much denser. The combination of SWOT data with data from three nadir altimeters provides a better resolution of wavelengths between 50 and 200 km with a more than 40% improvement outside tropical regions with respect to data from three nadir altimeters alone. The study has also highlighted that the impact of using SWOT data is likely to be very different depending on geographical areas. Constraining smaller spatial scales (wavelengths below 100 km) remains challenging as they are also associated with small time scales. Although this is only a first step, the study has demonstrated that SWOT data could be readily assimilated in a global high-resolution analysis and forecasting system with a positive impact at all latitudes and outstanding performances.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Ecosystems monitoring powered by environmental genomics: A review of current strategies with an implementation roadmap - Tristan Cordier; Laura Alonso‐Sáez; Laure Apothéloz‐Perret‐Gentil; Eva Aylagas; David A. Bohan; Agnès Bouchez; Anthony Chariton; Simon Creer; Larissa Frühe; François Keck; Nigel Keeley; Olivier Laroche; et al. (Molecular Ecology, 2021)
A decade after environmental scientists integrated high‐throughput sequencing technologies in their toolbox, the genomics‐based monitoring of anthropogenic impacts on the biodiversity and functioning of ecosystems is yet to be implemented by regulatory frameworks. Despite the broadly acknowledged potential of environmental genomics to this end, technical limitations and conceptual issues still stand in the way of its broad application by end‐users. In addition, the multiplicity of potential implementation strategies may contribute to a perception that the routine application of this methodology is premature or “in development”, hence restraining regulators from binding these tools into legal frameworks. Here, we review recent implementations of environmental genomics‐based methods, applied to the biomonitoring of ecosystems. By taking a general overview, without narrowing our perspective to particular habitats or groups of organisms, this paper aims to compare, review and discuss the strengths and limitations of four general implementation strategies of environmental genomics for monitoring: (a) Taxonomy‐based analyses focused on identification of known bioindicators or described taxa; (b) De novo bioindicator analyses; (c) Structural community metrics including inferred ecological networks; and (d) Functional community metrics (metagenomics or metatranscriptomics). We emphasise the utility of the three latter strategies to integrate meiofauna and microorganisms that are not traditionally utilised in biomonitoring because of difficult taxonomic identification. Finally, we propose a roadmap for the implementation of environmental genomics into routine monitoring programmes that leverage recent analytical advancements, while pointing out current limitations and future research needs.

Optimierung von Minibustaxiverkehren in Südafrika unter Einbindung von Geoinformationssystemen - Jan Schlüter; Leif Sörensen; Johannes Simons; Justin Coetzee (Standort, 2021)
Zusammenfassung Das Minibustaxi ist eines der wichtigsten Mobilitätsangebote in Südafrika. Allerdings sind Informationen, wie Fahrpläne oder -zeiten, aufgrund der hohen Flexibilität gar nicht oder nur selten verfügbar. Die damit einhergehenden Ineffizienzen, auch im Hinblick auf eine Abstimmung mit anderen Mobilitätsangeboten, können ohne Dokumentation des Status quo nur schwer behoben werden. Deshalb zeigt dieser Artikel exemplarisch am Beispiel Kapstadts, dass bereits einfache Methoden die Abbildung des Minibustaxiverkehrsnetzes ermöglichen und damit die Grundlage für Optimierungsansätze schaffen. Die Datenerfassung mittels einer mobilen Anwendung und die darauffolgende Auswertung zeigen, dass Effizienzsteigerungen im Minibustaxiverkehr von rund 30 % realisierbar wären. Neben dem operativen und gesamtwirtschaftlichen Einspar‑/Ertragsmöglichkeiten kann zusätzlich die potenzielle CO 2 -Emissionseinsparung angebracht werden. Dieser Artikel leistet ein wichtiges Argument für Formalisierungsansätze, um Effizienzsteigerungen im Mobilitätssektor gegenüber dem Status quo auch politisch vorantreiben zu können.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Isolated finger flexor vs. exhaustive whole-body climbing tests? How to assess endurance in sport climbers? - Jiří Baláš; Jan Gajdošík; David Giles; Simon Fryer; Dominika Krupková; Tomáš Brtník; Andri Feldmann (European Journal of Applied Physiology, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Hydraulic niche utilization by larvae of the three Drusinae clades (Insecta: Trichoptera) - Johann Waringer; Simon Vitecek; Jan Martini; Carina Zittra; Stephan Handschuh; Ariane Vieira; Hendrik C. Kuhlmann (Biologia, 2020)
Hydraulic niche descriptors of final instar larvae of nine Drusus species (Trichoptera) were studied in small, spring-fed, first-order headwaters located in the Mühlviertel (Upper Austria), Koralpe (Carinthia, Austria), and in the Austrian and Italian Alps. The species investigated covered all three clades of Drusinae: the shredder clade ( Drusus franzi , D. alpinus ), the grazer clade ( D. biguttatus , D. chauvinianus , D. dudor , D. monticola ), and the filtering carnivore clade ( D. chrysotus , D. katagelastos , D. muelleri ). Flow velocity was measured at front center of 68 larvae, head upstream, on the top of mineral substrate particles at water depths of 10–30 mm, using a tripod-stabilized Micro propeller meter (propeller diameter = 10 mm). Each data series consisted of a sampled measurement lasting 30 s (measuring interval = 1 s). In total, 2040 single velocity measurements were taken. Instantaneous flow velocities and drag at the sites of the 68 larvae varied from 0 to 0.93 m s −1 and 0 to 8346 *10 −6 N, respectively. Flow velocities and drag between the three clades were highly significantly different ( p + 95% confidence limits) for the three clades were 0.09 + 0.00 m s −1 for the shredder, 0.25 + 0.00 m s −1 for the grazer, and 0.31 + 0.01 m s −1 for the filtering carnivore clade; the corresponding data for drag were (85 + 18)*10 −6 N, (422 + 61)*10 −6 N and (1125 + 83)*10 −6 N, respectively. Adhesive friction ranged from (41.07 + 53.03)*10 −6 N in D. franzi to (255.24 + 216.87)*10 −6 N in D. chrysotus . Except in D. franzi and D. dudor adhesive friction was always well below drag force, indicating that submerged weight alone was not sufficient to stabilize the larvae in their hydraulic environment. Reynolds numbers varied between 0 in D. franzi and D. alpinus , and 12,634 in D. katagelastos , with 7% of the total in the laminar ( R R = 500–2000), and 61% in the fully turbulent stage ( R > 2000). Froude numbers ( Fr ) varied from 0 to 2.97. The two Drusus species of the shredder clade and three out of four species of the grazer clade were exposed to subcritical Fr 1.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Hydraulic stress parameters of a cased caddis larva (Drusus biguttatus) using spatio-temporally filtered velocity measurements - Johann Waringer; Simon Vitecek; Jan Martini; Carina Zittra; Stephan Handschuh; Ariane Vieira; Hendrik C. Kuhlmann (Hydrobiologia, 2020)
By studying hydraulic stress parameters of larvae of the cased caddisfly Drusus biguttatus (Pictet, 1834) in a tributary of the Schwarze Sulm (Carinthia, Austria), we aimed on (1) detecting the flow properties of the spatio-temporally filtered velocity measurements taken, and (2) on defining the hydraulic niche of this caddisfly larva. For this, we took 31 measurement series lasting 30 to 300 s, yielding 2176 single velocity measurements. The probability density functions of the 31 data series were Gaussian or sub-Gaussian, and the mean recurrent interval between velocity maxima within a data series was only 15.00 s. As a consequence, the Trichoptera larvae studied have to face strong flow accelerations in short intervals which is a much higher stress than conventional mean velocity measurements would suggest. The hydraulic niche of Drusus biguttatus is defined by instantaneous flow velocities ranging from 0.04 to 0.69 m s −1 , by drag forces from 13 × 10 −6 to 3737 × 10 −6 N, by Froude numbers from 0.13 to 1.20, and mostly by Reynolds numbers > 2000. Under such conditions, only 5.1% of the drag force is compensated by submerged weight, whereas the remainder has to be counterbalanced by the active efforts of the larvae to remain attached to the substrate.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

Accuracy of crowdsourced streamflow and stream level class estimates - Barbara Strobl; Simon Etter; Ilja van Meerveld; Jan Seibert (Hydrological Sciences Journal, 2020)

The Production, Quality Control, and Characterization of ZED8, a CD8-Specific 89Zr-Labeled Immuno-PET Clinical Imaging Agent - Herman Gill; Richard Seipert; Vincent M. Carroll; Alexandra Gouasmat; Jian Yin; Annie Ogasawara; Isabella de Jong; Minh Michael Phan; Xiangdan Wang; Jihong Yang; Ohad Ilovich; Jan Marik; et al. (The AAPS Journal, 2020)

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

Return of the moth: rethinking the effect of climate on insect outbreaks - Ulf Büntgen; Andrew Liebhold; Daniel Nievergelt; Beat Wermelinger; Alain Roques; Frederick Reinig; Paul J. Krusic; Alma Piermattei; Simon Egli; Paolo Cherubini; Jan Esper (Oecologia, 2020)
The sudden interruption of recurring larch budmoth (LBM; Zeiraphera diniana or griseana Gn.) outbreaks across the European Alps after 1982 was surprising, because populations had regularly oscillated every 8–9 years for the past 1200 years or more. Although ecophysiological evidence was limited and underlying processes remained uncertain, climate change has been indicated as a possible driver of this disruption. An unexpected, recent return of LBM population peaks in 2017 and 2018 provides insight into this insect’s climate sensitivity. Here, we combine meteorological and dendrochronological data to explore the influence of temperature variation and atmospheric circulation on cyclic LBM outbreaks since the early 1950s. Anomalous cold European winters, associated with a persistent negative phase of the North Atlantic Oscillation, coincide with four consecutive epidemics between 1953 and 1982, and any of three warming-induced mechanisms could explain the system’s failure thereafter: (1) high egg mortality, (2) asynchrony between egg hatch and foliage growth, and (3) upward shifts of outbreak epicentres. In demonstrating that LBM populations continued to oscillate every 8–9 years at sub-outbreak levels, this study emphasizes the relevance of winter temperatures on trophic interactions between insects and their host trees, as well as the importance of separating natural from anthropogenic climate forcing on population behaviour.

Development of a neural rosette formation assay (RoFA) to identify neurodevelopmental toxicants and to characterize their transcriptome disturbances - Nadine Dreser; Katrin Madjar; Anna-Katharina Holzer; Marion Kapitza; Christopher Scholz; Petra Kranaster; Simon Gutbier; Stefanie Klima; David Kolb; Christian Dietz; Timo Trefzer; Johannes Meisig; et al. (Archives of Toxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Faster speciation of fig‐wasps than their host figs leads to decoupled speciation dynamics: Snapshots across the speciation continuum - Daniel Souto‐Vilarós; Antonin Machac; Jan Michalek; Clive Terence Darwell; Mentap Sisol; Thomas Kuyaiva; Brus Isua; George D. Weiblen; Vojtech Novotny; Simon T. Segar (Molecular Ecology, 2019)
Even though speciation involving multiple interacting partners, such as plants and their pollinators, has attracted much research, most studies focus on isolated phases of the process. This currently precludes an integrated understanding of the mechanisms leading to cospeciation. Here, we examine population genetic structure across six species‐pairs of figs and their pollinating wasps along an elevational gradient in New Guinea. Specifically, we test three hypotheses on the genetic structure within the examined species‐pairs and find that the hypothesized genetic structures represent different phases of a single continuum, from incipient cospeciation to the full formation of new species. Our results also illuminate the mechanisms governing cospeciation, namely that fig wasps tend to accumulate population genetic differences faster than their figs, which initially decouples the speciation dynamics between the two interacting partners and breaks down their one‐to‐one matching. This intermediate phase is followed by genetic divergence of both partners, which may eventually restore the one‐to‐one matching among the fully formed species. Together, these findings integrate current knowledge on the mechanisms operating during different phases of the cospeciation process. They also reveal that the increasingly reported breakdowns in one‐to‐one matching may be an inherent part of the cospeciation process. Mechanistic understanding of this process is needed to explain how the extraordinary diversity of species, especially in the tropics, has emerged. Knowing which breakdowns in species interactions are a natural phase of cospeciation and which may endanger further generation of diversity seems critical in a constantly changing world.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The European Marine Observation and Data Network (EMODnet): Visions and Roles of the Gateway to Marine Data in Europe - Belén Martín Míguez; Antonio Novellino; Matteo Vinci; Simon Claus; Jan-Bart Calewaert; Henry Vallius; Thierry Schmitt; Alessandro Pititto; Alessandra Giorgetti; Natalie Askew; Sissy Iona; Dick Schaap; et al. (Frontiers in Marine Science, 2019)

Systemic Exposure of Rituximab Increased by Ibrutinib: Pharmacokinetic Results and Modeling Based on the HELIOS Trial - Silvia Maria Lavezzi; Jan de Jong; Martine Neyens; Paula Cramer; Fatih Demirkan; Graeme Fraser; Nancy Bartlett; Marie-Sarah Dilhuydy; Javier Loscertales; Abraham Avigdor; Simon Rule; Olga Samoilova; et al. (Pharmaceutical Research, 2019)

The anti-bacterial iron-restriction defence mechanisms of egg white; the potential role of three lipocalin-like proteins in resistance against Salmonella - Louis Alex Julien; Florence Baron; Sylvie Bonnassie; Françoise Nau; Catherine Guérin; Sophie Jan; Simon Colin Andrews (BioMetals, 2019)

Domestic gardens play a dominant role in selecting alien species with adaptive strategies that facilitate naturalization - Wen‐Yong Guo; Mark van Kleunen; Simon Pierce; Wayne Dawson; Franz Essl; Holger Kreft; Noëlie Maurel; Jan Pergl; Hanno Seebens; Patrick Weigelt; Petr Pyšek (Global Ecology and Biogeography, 2019)
Aim Horticulture has been recognized as the main pathway of plant invasions worldwide. The selection of ornamental garden plants is not random, and certain plant characteristics related to adaptive plant strategies are preferred by horticulture and may promote invasion. We examined the direct and indirect interactions between horticultural use, species adaptive strategies (competitive (C), stress‐tolerant (S), and ruderal (R)), native range size and naturalization success. Location Global. Time period From 1492 to the present. Major taxa studied Vascular plants. Methods We compiled a dataset of 3,794 plant species including their C‐, S‐ and R‐scores, native range size, cultivation in botanic and domestic gardens and whether the species is naturalized in at least one region globally (naturalization incidence). For the 1,711 naturalized species, we also calculated naturalization extent, that is, the number of regions where the species has naturalized. We used phylogenetic path analysis to disentangle the direct and indirect effects of all variables on both naturalization incidence and extent, and the relationships between variables. Results Approximately 87 and 94% of the 1,711 naturalized species were cultivated in botanic or domestic gardens, respectively, compared to c . 55 and 50% of the 2,083 non‐naturalized species, respectively. We found a cascading structure among the examined variables: (a) species exhibiting C‐ or R‐selected strategies and having large native ranges tended to be cultivated in domestic and botanic gardens, became naturalized outside their native ranges and occupied more regions in their naturalized ranges; (b) C‐, S‐ and R‐scores also had indirect effects on naturalization success, which were mediated by horticultural use and native range size; and (c) cultivation in domestic gardens was the strongest factor examined that could explain plant species’ naturalization success. Main conclusions We show that horticulture is not only the major introduction pathway of alien plants, but also that in particular domestic gardens select species predisposed to invade and naturalize.

High growth potential of Ailanthus altissima in warm and dry weather conditions in novel forests of southern Switzerland - Simon Knüsel; Marco Conedera; Roman Zweifel; Harald Bugmann; Sophia Etzold; Jan Wunder (Trees, 2019)

Ivabradine Aggravates the Proarrhythmic Risk in Experimental Models of Long QT Syndrome - Gerrit Frommeyer; Jan Weller; Christian Ellermann; Patrick Leitz; Simon Kochhäuser; Philipp S. Lange; Dirk G. Dechering; Lars Eckardt (Cardiovascular Toxicology, 2019)

DNA metabarcoding—Need for robust experimental designs to draw sound ecological conclusions - Lucie Zinger; Aurélie Bonin; Inger G. Alsos; Miklós Bálint; Holly Bik; Frédéric Boyer; Anthony A. Chariton; Simon Creer; Eric Coissac; Bruce E. Deagle; Marta De Barba; Ian A. Dickie; et al. (Molecular Ecology, 2019)

Rapid gene cloning in cereals - Jan Bettgenhaeuser; Simon G. Krattinger (Theoretical and Applied Genetics, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

Mononuclear-cell-derived microparticles attenuate endothelial inflammation by transfer of miR-142-3p in a CD39 dependent manner - Stephanie Kuhn; Katrin Splith; Cindy Ballschuh; Linda Feldbrügge; Felix Krenzien; Georgi Atanasov; Christian Benzing; Hans-Michael Hau; Cornelius Engelmann; Thomas Berg; Jan Schulte am Esch; Johann Pratschke; et al. (Purinergic Signalling, 2018)

Effects of tapeworm infection on absorption and excretion of zinc and cadmium by experimental rats - Vladislav Sloup; Ivana Jankovská; Jiřina Száková; Jan Magdálek; Simon Sloup; Iva Langrová (Environmental Science and Pollution Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Football practice with youth players in the “Footbonaut” - Tobias Vogt; Simon Gassen; Sören Wrede; Jan Spielmann; Martin Jedrusiak-Jung; Sascha Härtel; Jan Mayer (German Journal of Exercise and Sport Research, 2018)

Particulate matter flux interception in oceanic mesoscale eddies by the polychaete Poeobius sp. - Svenja Christiansen; Henk‐Jan Hoving; Florian Schütte; Helena Hauss; Johannes Karstensen; Arne Körtzinger; Simon‐Martin Schröder; Lars Stemmann; Bernd Christiansen; Marc Picheral; Peter Brandt; Bruce Robison; et al. (Limnology and Oceanography, 2018)
Gelatinous zooplankton hold key functions in the ocean and have been shown to significantly influence the transport of organic carbon to the deep sea. We discovered a gelatinous, flux‐feeding polychaete of the genus Poeobius in very high abundances in a mesoscale eddy in the tropical Atlantic Ocean, where it co‐occurred with extremely low particle concentrations. Subsequent analysis of an extensive in situ imaging dataset revealed that Poeobius sp. occurred sporadically between 5°S–20°N and 16°W–46°W in the upper 1000 m. Abundances were significantly elevated and the depth distribution compressed in anticyclonic modewater eddies (ACMEs). In two ACMEs, high Poeobius sp. abundances were associated with strongly reduced particle concentrations and fluxes in the layers directly below the polychaete. We discuss possible reasons for the elevated abundances of Poeobius sp. in ACMEs and provide estimations showing that a single zooplankton species can completely intercept the downward particle flux by feeding with their mucous nets, thereby substantially altering the biogeochemical setting within the eddy.

The role of adaptive strategies in plant naturalization - Wen‐Yong Guo; Mark van Kleunen; Marten Winter; Patrick Weigelt; Anke Stein; Simon Pierce; Jan Pergl; Dietmar Moser; Noëlie Maurel; Bernd Lenzner; Holger Kreft; Franz Essl; et al. (Ecology Letters, 2018)
Determining the factors associated with the naturalization of alien species is a central theme in ecology. Here, we tested the usefulness of a metric for quantifying Grime's seminal concept of adaptive strategies – competitors, stress‐tolerators and ruderals ( CSR ) – to explain plant naturalizations worldwide. Using a global dataset of 3004 vascular plant species, and accounting for phylogenetic relatedness and species’ native biomes, we assessed the associations between calculated C‐, S‐ and R‐scores and naturalization success for species exhibiting different life forms. Across different plant life forms, C‐scores were positively and S‐scores negatively associated with both the probability of naturalization and the number of regions where the species has naturalized. R‐scores had positive effects on the probability of naturalization. These effects of the scores were, however, weak to absent for tree species. Our findings demonstrate the utility of CSR ‐score calculation to broadly represent, and potentially explain, the naturalization success of plant species.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Biochronological and palaeobiogeographical significance of the earliest Miocene mammal fauna from Northern Vietnam - Jérôme Prieto; Pierre-Olivier Antoine; Jan van der Made; Grégoire Métais; Laq The Phuc; Quý Trương Quan; Simon Schneider; Dang Ngoc Tran; Davit Vasilyan; Luong The Viet; Madelaine Böhme (Palaeobiodiversity and Palaeoenvironments, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Responses of medullary lateral line units of the rudd, Scardinius erythrophthalmus, and the nase, Chondrostoma nasus, to vortex streets - Jan Winkelnkemper; Simon Kranz; Horst Bleckmann (Journal of Comparative Physiology A, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Community structure of insect herbivores is driven by conservatism, escalation and divergence of defensive traits in Ficus - Martin Volf; Simon T. Segar; Scott E. Miller; Brus Isua; Mentap Sisol; Gibson Aubona; Petr Šimek; Martin Moos; Juuso Laitila; Jorma Kim; Jan Zima; Jadranka Rota; et al. (Ecology Letters, 2018)
Escalation (macroevolutionary increase) or divergence (disparity between relatives) in trait values are two frequent outcomes of the plant‐herbivore arms race. We studied the defences and caterpillars associated with 21 sympatric New Guinean figs. Herbivore generalists were concentrated on hosts with low protease and oxidative activity. The distribution of specialists correlated with phylogeny, protease and trichomes. Additionally, highly specialised Asota moths used alkaloid rich plants. The evolution of proteases was conserved, alkaloid diversity has escalated across the studied species, oxidative activity has escalated within one clade, and trichomes have diverged across the phylogeny. Herbivore specificity correlated with their response to host defences: escalating traits largely affected generalists and divergent traits specialists; but the effect of escalating traits on extreme specialists was positive. In turn, the evolution of defences in Ficus can be driven towards both escalation and divergence in individual traits, in combination providing protection against a broad spectrum of herbivores.

A deletion of the gene encoding amino aldehyde dehydrogenase enhances the “pandan-like” aroma of winter melon (Benincasa hispida) and is a functional marker for the development of the aroma - Saowalak Ruangnam; Samart Wanchana; Nongnat Phoka; Chatree Saeansuk; Sugunya Mahatheeranont; Simon Jan de Hoop; Theerayut Toojinda; Apichart Vanavichit; Siwaret Arikit (Theoretical and Applied Genetics, 2017)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Quality‐assured long‐term satellite‐based leaf area index product - Jian Peng; Simon Blessing; Ralf Giering; Benjamin Müller; Nadine Gobron; Joanne Nightingale; Folkert Boersma; Jan‐Peter Muller (Global Change Biology, 2017)

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Sensitivity of unmanaged relict pine forest in the Czech Republic to climate change and air pollution - Stanislav Vacek; Zdeněk Vacek; Jiří Remeš; Lukáš Bílek; Iva Hůnová; Daniel Bulušek; Tereza Putalová; Jan Král; Jaroslav Simon (Trees, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Diversity and biogeography of arbuscular mycorrhizal fungi in agricultural soils - Fritz Oehl; Endre Laczko; Hans-Rudolf Oberholzer; Jan Jansa; Simon Egli (Biology and Fertility of Soils, 2017)

Indirect effects of bottom fishing on the productivity of marine fish - Jeremy Collie; Jan Geert Hiddink; Tobias van Kooten; Adriaan D Rijnsdorp; Michel J Kaiser; Simon Jennings; Ray Hilborn (Fish and Fisheries, 2017)
One quarter of marine fish production is caught with bottom trawls and dredges on continental shelves around the world. Towed bottom‐fishing gears typically kill 20–50 per cent of the benthic invertebrates in their path, depending on gear type, substrate and vulnerability of particular taxa. Particularly vulnerable are epifaunal species, which stabilize the sediment and provide habitat for benthic invertebrates. To identify the habitats, fisheries or target species most likely to be affected, we review evidence of the indirect effects of bottom fishing on fish production. Recent studies have found differences in the diets of certain species in relation to bottom fishing intensity, thereby linking demersal fish to their benthic habitats at spatial scales of ~10 km. Bottom fishing affects diet composition and prey quality rather than the amount of prey consumed; scavenging of discarded by‐catch makes only a small contribution to yearly food intake. Flatfish may benefit from light trawling levels on sandy seabeds, while higher‐intensity trawling on more vulnerable habitats has a negative effect. Models suggest that reduction in the carrying capacity of habitats by bottom fishing could lead to lower equilibrium yield and a lower level of fishing mortality to obtain maximum yield. Trawling effort is patchily distributed – small fractions of fishing grounds are heavily fished, while large fractions are lightly fished or unfished. This patchiness, coupled with the foraging behaviour of demersal fish, may mitigate the indirect effects of bottom fishing on fish productivity. Current research attempts to scale up these localized effects to the population level.

Initial biochar effects on plant productivity derive from N fertilization - Simon Jeffery; Ilse Memelink; Edward Hodgson; Sian Jones; Tess F. J. van de Voorde; T. Martijn Bezemer; Liesje Mommer; Jan Willem van Groenigen (Plant and Soil, 2017)

Exome analysis of Smith–Magenis-like syndrome cohort identifies de novo likely pathogenic variants - Seth I. Berger; Carla Ciccone; Karen L. Simon; May Christine Malicdan; Thierry Vilboux; Charles Billington; Roxanne Fischer; Wendy J. Introne; Andrea Gropman; Jan K. Blancato; James C. Mullikin; William A. Gahl; et al. (Human Genetics, 2017)

Shade tolerance of Ailanthus altissima revisited: novel insights from southern Switzerland - Simon Knüsel; Andrea De Boni; Marco Conedera; Patrick Schleppi; Jean-Jacques Thormann; Monika Frehner; Jan Wunder (Biological Invasions, 2017)

Genetic analyses of the functions of [NiFe]-hydrogenase maturation endopeptidases in the hyperthermophilic archaeon Thermococcus kodakarensis - Tamotsu Kanai; Ayako Yasukochi; Jan-Robert Simons; Joseph Walker Scott; Wakao Fukuda; Tadayuki Imanaka; Haruyuki Atomi (Extremophiles, 2017)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Worldwide Analysis of Sedimentary DNA Reveals Major Gaps in Taxonomic Knowledge of Deep-Sea Benthos - Frédéric Sinniger; Jan Pawlowski; Saki Harii; Andrew J. Gooday; Hiroyuki Yamamoto; Pierre Chevaldonné; Tomas Cedhagen; Gary Carvalho; Simon Creer (Frontiers in Marine Science, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Forest restoration following surface mining disturbance: challenges and solutions - S. Ellen Macdonald; Simon M. Landhäusser; Jeff Skousen; Jennifer Franklin; Jan Frouz; Sarah Hall; Douglass F. Jacobs; Sylvie Quideau (New Forests, 2015)

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Prevalence of the BLM nonsense mutation, p.Q548X, in ovarian cancer patients from Central and Eastern Europe - Natalia Bogdanova; Alexandr V. Togo; Magdalena Ratajska; Wojtek Kluźniak; Zalina Takhirova; Theresa Tarp; Darya Prokofyeva; Marina Bermisheva; Grigoriy A. Yanus; Tatiana V. Gorodnova; Anna P. Sokolenko; Alina Kuźniacka; et al. (Familial Cancer, 2015)

Intensive agriculture reduces soil biodiversity across Europe - Maria A. Tsiafouli; Elisa Thébault; Stefanos P. Sgardelis; Peter C. de Ruiter; Wim H. van der Putten; Klaus Birkhofer; Lia Hemerik; Franciska T. de Vries; Richard D. Bardgett; Mark Vincent Brady; Lisa Bjornlund; Helene Bracht Jørgensen; et al. (Global Change Biology, 2015)
Soil biodiversity plays a key role in regulating the processes that underpin the delivery of ecosystem goods and services in terrestrial ecosystems. Agricultural intensification is known to change the diversity of individual groups of soil biota, but less is known about how intensification affects biodiversity of the soil food web as a whole, and whether or not these effects may be generalized across regions. We examined biodiversity in soil food webs from grasslands, extensive, and intensive rotations in four agricultural regions across Europe: in Sweden, the UK , the Czech Republic and Greece. Effects of land‐use intensity were quantified based on structure and diversity among functional groups in the soil food web, as well as on community‐weighted mean body mass of soil fauna. We also elucidate land‐use intensity effects on diversity of taxonomic units within taxonomic groups of soil fauna. We found that between regions soil food web diversity measures were variable, but that increasing land‐use intensity caused highly consistent responses. In particular, land‐use intensification reduced the complexity in the soil food webs, as well as the community‐weighted mean body mass of soil fauna. In all regions across Europe, species richness of earthworms, Collembolans, and oribatid mites was negatively affected by increased land‐use intensity. The taxonomic distinctness, which is a measure of taxonomic relatedness of species in a community that is independent of species richness, was also reduced by land‐use intensification. We conclude that intensive agriculture reduces soil biodiversity, making soil food webs less diverse and composed of smaller bodied organisms. Land‐use intensification results in fewer functional groups of soil biota with fewer and taxonomically more closely related species. We discuss how these changes in soil biodiversity due to land‐use intensification may threaten the functioning of soil in agricultural production systems.

Transcriptional profiling of G ram‐positive A rthrobacter in the phyllosphere: induction of pollutant degradation genes by natural plant phenolic compounds - Tanja R. Scheublin; Simon Deusch; Silvia K. Moreno‐Forero; Jochen A. Müller; Jan Roelof van der Meer; Johan H. J. Leveau (Environmental Microbiology, 2014)
Summary A rthrobacter chlorophenolicus A 6 is a G ram‐positive, 4‐chlorophenol‐degrading soil bacterium that was recently shown to be an effective colonizer of plant leaf surfaces. The genetic basis for this phyllosphere competency is unknown. In this paper, we describe the genome‐wide expression profile of A . chlorophenolicus on leaves of common bean ( P haseolus vulgaris ) compared with growth on agar surfaces. In phyllosphere‐grown cells, we found elevated expression of several genes known to contribute to epiphytic fitness, for example those involved in nutrient acquisition, attachment, stress response and horizontal gene transfer. A surprising result was the leaf‐induced expression of a subset of the so‐called cph genes for the degradation of 4‐chlorophenol. This subset encodes the conversion of the phenolic compound hydroquinone to 3‐oxoadipate, and was shown to be induced not only by 4‐chlorophenol but also hydroquinone, its glycosylated derivative arbutin, and phenol. Small amounts of hydroquinone, but not arbutin or phenol, were detected in leaf surface washes of P . vulgaris by gas chromatography‐mass spectrometry. Our findings illustrate the utility of genomics approaches for exploration and improved understanding of a microbial habitat. Also, they highlight the potential for phyllosphere‐based priming of bacteria to stimulate pollutant degradation, which holds promise for the application of phylloremediation.

New Insight into Neurodegeneration: the Role of Proteomics - Ramavati Pal; Guido Alves; Jan Petter Larsen; Simon Geir Møller (Molecular Neurobiology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Marine Regions: Towards a Global Standard for Georeferenced Marine Names and Boundaries - Simon Claus; Nathalie De Hauwere; Bart Vanhoorne; Pieter Deckers; Francisco Souza Dias; Francisco Hernandez; Jan Mees (Marine Geodesy, 2014)

Soil and geography are more important determinants of indigenous arbuscular mycorrhizal communities than management practices in Swiss agricultural soils - Jan Jansa; Angela Erb; Hans‐Rudolf Oberholzer; Petr Šmilauer; Simon Egli (Molecular Ecology, 2014)
Arbuscular mycorrhizal fungi ( AMF ) are ubiquitous soil fungi, forming mutualistic symbiosis with a majority of terrestrial plant species. They are abundant in nearly all soils, less diverse than soil prokaryotes and other intensively studied soil organisms and thus are promising candidates for universal indicators of land management legacies and soil quality degradation. However, insufficient data on how the composition of indigenous AMF varies along soil and landscape gradients have hampered the definition of baselines and effect thresholds to date. Here, indigenous AMF communities in 154 agricultural soils collected across Switzerland were profiled by quantitative real‐time PCR with taxon‐specific markers for six widespread AMF species. To identify the key determinants of AMF community composition, the profiles were related to soil properties, land management and site geography. Our results indicate a number of well‐supported dependencies between abundances of certain AMF taxa and soil properties such as pH , soil fertility and texture, and a surprising lack of effect of available soil phosphorus on the AMF community profiles. Site geography, especially the altitude and large geographical distance, strongly affected AMF communities. Unexpected was the apparent lack of a strong land management effect on the AMF communities as compared to the other predictors, which could be due to the rarity of highly intensive and unsustainable land management in Swiss agriculture. In spite of the extensive coverage of large geographical and soil gradients, we did not identify any taxon suitable as an indicator of land use among the six taxa we studied.

Evolution of MHC class I in the Order Crocodylia - Weerachai Jaratlerdsiri; Sally R. Isberg; Damien P. Higgins; Simon Y. W. Ho; Jan Salomonsen; Karsten Skjodt; Lee G. Miles; Jaime Gongora (Immunogenetics, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Volume Estimation of the Thalamus Using Freesurfer and Stereology: Consistency between Methods - Simon S. Keller; Jan S. Gerdes; Siawoosh Mohammadi; Christoph Kellinghaus; Harald Kugel; Katja Deppe; E. Bernd Ringelstein; Stefan Evers; Wolfram Schwindt; Michael Deppe (Neuroinformatics, 2012)

Effects of dexamphetamine with and without alcohol on simulated driving - Ries Simons; Marieke Martens; Jan Ramaekers; Arno Krul; Ineke Klöpping-Ketelaars; Gisela Skopp (Psychopharmacology, 2012)

Regenerative potential of glycosaminoglycans for skin and bone - Juliane Salbach; Tilman D. Rachner; Martina Rauner; Ute Hempel; Ulf Anderegg; Sandra Franz; Jan-Christoph Simon; Lorenz C. Hofbauer (Journal of Molecular Medicine, 2012)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Flupirtine is a safe alternative drug in patients with hypersensitivity to NSAIDs - Regina Treudler; Katja Pohle; Jan Christoph Simon (European Journal of Clinical Pharmacology, 2011)

Erratum to: Analysing the content of the European Ocean Biogeographic Information System (EurOBIS): available data, limitations, prospects and a look at the future - Leen Vandepitte; Francisco Hernandez; Simon Claus; Bart Vanhoorne; Nathalie De Hauwere; Klaas Deneudt; Ward Appeltans; Jan Mees (Hydrobiologia, 2011)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

Analysing the content of the European Ocean Biogeographic Information System (EurOBIS): available data, limitations, prospects and a look at the future - Leen Vandepitte; Francisco Hernandez; Simon Claus; Bart Vanhoorne; Nathalie De Hauwere; Klaas Deneudt; Ward Appeltans; Jan Mees (Hydrobiologia, 2011)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Thermal expansion and high-temperature P21/c–C2/c phase transition in clinopyroxene-type LiFeGe2O6 and comparison to NaFe(Si,Ge)2O6 - Günther J. Redhammer; Fernando Cámara; Matteo Alvaro; Fabrizio Nestola; Gerold Tippelt; Sebastian Prinz; Jan Simons; Georg Roth; Georg Amthauer (Physics and Chemistry of Minerals, 2010)

Comparative analysis of the widespread and conserved PB1‐like viruses infecting Pseudomonas aeruginosa - Pieter‐Jan Ceyssens; Konstantin Miroshnikov; Wesley Mattheus; Victor Krylov; Johan Robben; Jean‐Paul Noben; Simon Vanderschraeghe; Nina Sykilinda; Andrew M. Kropinski; Guido Volckaert; Vadim Mesyanzhinov; Rob Lavigne (Environmental Microbiology, 2009)
Summary We examined the genetic diversity of lytic Pseudomonas aeruginosa bacteriophage PB1 and four closely related phages (LBL3, LMA2, 14‐1 and SN) isolated throughout Europe. They all encapsulate linear, non‐permuted genomes between 64 427 and 66 530 bp within a solid, acid‐resistant isometric capsid (diameter: 74 nm) and carry non‐flexible, contractile tails of approximately 140 nm. The genomes are organized into at least seven transcriptional blocks, alternating on both strands, and encode between 88 (LBL3) and 95 (LMA2) proteins. Their virion particles are composed of at least 22 different proteins, which were identified using mass spectrometry. Post‐translational modifications were suggested for two proteins, and a frameshift hotspot was identified within ORF 42 , encoding a structural protein. Despite large temporal and spatial separations between phage isolations, very high sequence similarity and limited horizontal gene transfer were found between the individual viruses. These PB1‐like viruses constitute a new genus of environmentally very widespread phages within the Myoviridae .

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Wave Energy from the North Sea: Experiences from the Lysekil Research Site - Mats Leijon; Cecilia Boström; Oskar Danielsson; Stefan Gustafsson; Kalle Haikonen; Olivia Langhamer; Erland Strömstedt; Magnus Stålberg; Jan Sundberg; Olle Svensson; Simon Tyrberg; Rafael Waters (Surveys in Geophysics, 2008)

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Identity-by-descent approach to gene localisation in eight individuals affected by keratoconus from north-west Tasmania, Australia - Jan Fullerton; Patricia Paprocki; Simon Foote; David A. Mackey; Robert Williamson; Susan Forrest (Human Genetics, 2002)

Propagule bank buildup of Chara aspera and its significance for colonization of a shallow lake - Marcel S. Van den Berg; Hugo Coops; Jan Simons (Hydrobiologia, 2001)

Macroinvertebrate communities in relation to submerged vegetation in two Chara-dominated lakes - Marcel S. van den Berg; Hugo Coops; Ruurd Noordhuis; John van Schie; Jan Simons (Hydrobiologia, 1997)

Restoration of Botshol (The Netherlands) by reduction of external nutrient load: Recovery of the Characean community - Jan Simons; Marieke Ohm; Remco Daalder (Aquatic Ecology, 1992)